DIGITAL TRANSFORMATION AS AN EFFORT TO IMPROVE EQUITY AND AFFORDABILITY OF HEALTH INFORMATION SERVICES - suhendra vmi, adi (Jurnal Studi Inovasi, 2025)
This research is about digital transformation as an effort to equalize and affordability of health information services through the Free Internet Service Program for Communities to Remote Border Areas (ROMANTIS MANTAP CIL) in North Kalimantan Province, Electronic Vehicle for Community Health Across Citizen Users ( WEKAR LAWA) in West Manggarai Regency and Integrated Development Post and Integrated Elderly Posyandu Mobile Health Center, Acupressure and Sports Health (POSBIDUAN LANGSINGKU KESOHOR) in South Bangka Regency. The ROMANTIS MANTAP CIL innovation is the provision of internet facilities through Wifi media that can be accessed by the public for free in every Regency and City in North Kalimantan Province. The WEKAR LAWA innovation is an ecosystem for managing health services based on information technology, in order to produce reliable and easily accessible health data and information, as well as increase the effectiveness and efficiency of implementing health service efforts, as part of supporting the creation of a smart life, especially in the health sector (smart health living). The innovation of POSBIDUAN LANGSINGKU KESOHOR is an effort to equalize and affordably provide health services for the community down to the village/hamlet level, by integrating the facilities of the Mobile Health Center, Integrated Development Post and Elderly Posyandu with acupressure and sports health. These three innovations have given rise to various strategies that offer convenience in the implementation of government activities in health services. This study uses a qualitative approach research method. The data collection technique uses a literature review . A literature review is a systematic examination of critical scientific literature in analyzing, evaluating, and synthesizing research findings, theories, and practices. Literature review provides an overview of the development of a particular topic. Digital transformation produces innovations that can improve health services, including: the results of the ROMANTIS MANTAP CIL innovation are the availability of internet accessibility services to support health services for communities in remote, border, and isolated areas in North Kalimantan Province. The results of the WEKAR LAWA innovation are the availability of web-based health information systems, including the Health Center and Network Information System (e-Puskesmas), the District Health Office Information System (e-Dinkes). Then the android-based information system is the android-based online patient registration system (e-Registration). All three are running well, producing reliable health data and information, easy to access and more effective and efficient. The results of the POSBIDUAN LANGSINGKU KESOHOR innovation are through Mobile Health Centers directly coming to Villages/Hamlets, can detect Diabetes Mellitus and Hypertension, provide health education to the community, get the community used to exercise, provide guidance to productive elderly people, and IVA examinations as early detection of cervical cancer.